ANALISIS EFISIENSI PACKAGE BOILER 2011 UA DENGAN KAPASITAS 50 TON/JAM PT. PERTAMINA REFINERY UNIT III PLAJU SUMATERA SELATAN - Arkan Mahadi (2021)
Efficiency is one of the efforts in saving energy sources for the future. Efficiency in the boiler is a work level obtained from the fluid energy transfer process in the boiler by adding the fuel it uses. This research was conducted with the aim of knowing the magnitude of the boiler efficiency, namely Package Boiler 2011 UA which is fueled by mixed gas. Then this research also aims to find out what factors affect the decrease in efficiency. This research was conducted using 2 methods to calculate boiler efficiency, namely direct and indirect methods. The direct method directly compares the boiler input and output, while the indirect method focuses on heat loss. With average results ranging from 93% for the direct method and 91% for the indirect method, it can be concluded that the boiler has been running well. The direct method focuses more on when there is a decrease in efficiency in the boiler, while the indirect method is suitable for knowing in detail what factors affect the decline in the boiler. Then the most significant heatloss factor in reducing the efficiency of this boiler is the moisture contained in the fuel.